Steep : the Precipitous Rise of the Tea Party - Rosenthal, Lawrence, 1949-; Trost, Christine (University of California Press, 2012)
In the Spring of 2009, the Tea Party emerged onto the American political scene. In the wake of Obama's election, as commentators proclaimed the "death of conservatism," Tax Day rallies and Tea Party showdowns at congressional town hall meetings marked a new and unexpected chapter in American conservatism. Accessible to students and general readers, Steep: The Precipitous Rise of the Tea Party brings together leading scholars and experts on the American Right to examine a political movement that electrified American society. Topics addressed by the volume's contributors include the Tea Party's.